Electrodeposition of Zinc Nanorods from Ionic Liquid into Porous Anodic Alumina - Starykevich, Maksim
Electrochemical deposition of zinc nanorods into the anodic aluminium-oxide template from ionic-liquid electrolyte is reported. For the first time, the electrodeposition from an ionic liquid is performed in a porous alumina template, anodically grown on the aluminium substrate without complete removal of the barrier layer. The two-step process was applied; first, with alternating-current pulse nucleation of zinc nanoparticles on the bottom of the pores, followed by direct-current growth of the rods. The electrolyte consisted of 0.5 M ZnCl2 in choline chloride and ethylene glycol in a 1:2 molar ratiod. The resulting zinc nanorods are approximately 3 mu m in length and 70 nm in diameter. The achieved fill factor of the pores is in the 70-80 % range.